Cytogenetical and cytotaxonomical analysis of some Brazilian species of Eleocharis (Cyperaceae) - Maximiano da Silva, Carlos Roberto [UNESP]; Socorro Gonzalez-Elizondo, Maria; Andrade de Almeida Rego, Leticia do Nascimento; Domingues Torezan, Jose Marcelo; Laforga Vanzela, Andre Luis (CSIRO Publishing, 2008)
Karyotype analysis of 21 samples of 11 species of Eleocharis ( Cyperaceae) from 10 localities in Brazil, showed the presence of chromosomes without primary constrictions and parallel movement of chromatids at metaphase-anaphase transition. Only the terminal nucleolar constrictions ( satellites) were visualised. The chromosome numbers varied from 2n=6 in E. subarticulata to 2n=54 in E. acutangula, but the chromosome basic number x=5 was confirmed. Generally, C-CMA(3)(+) bands appear mostly in the extremities of the chromosomes, associated to NOR, and interstitial C-CMA(3) bands were found only in E. geniculata and E. acutangula. C-DAPI(+) bands were not found. Fluorescence in situ hybridisation ( FISH) with the 45S rDNA probe was performed in five species. The results showed from four to eight hybridisation signals, always terminal. The analysed species include representatives of the following three subgenera of Eleocharis that occur in Brazil: Limnochloa, Scirpidium and Eleocharis. Species from the subgenus Limnochloa have small and numerous chromosomes. The remaining species, belonging to subgenera Eleocharis and Scirpidium, possess fewer and larger chromosomes. In subgenus Eleocharis, karyotypes of the section Eleocharis were differentiated by symploidy, agmatoploidy and polyploidy, whereas species of the section Eleogenus were all polyploids. Polyploidy seems to be the most frequent event in the karyotype differentiation in Eleocharis, but changes in the chromosome size and repetitive DNA sites were also observed.